Storytelling Islami untuk Karakter Anak Usia Dini: Studi Al-Qiṣaṣ Al-Hādifah pada Dawr Mu‘Allim At-Tarbiyah Al-Islāmiyyah Al-Fāyiz - Abdah Munfaridatus Sholihah; Basuki Basuki (Institut Agama Islam Sunan Giri Ponorogo, 2026)
Early childhood character formation is an important foundation for future human development because moral values, empathy, and social behavior begin to take shape during this time. Theoretically, character education emphasizes the integration between the aspects of moral knowing, moral feeling, and moral action that are instilled through a conducive educational environment. However, social reality shows that there is a gap between the ideal concept and the conditions on the ground. Various media reports show an increase in cases of bullying, digital aggressiveness, and declining manners in early childhood influenced by unsupervised exposure to technology and weak moral examples. This condition poses a risk of emotional regulation disorders, decreased quality of social relationships, and weakening of children's religious identity. Therefore, an effective educational approach is needed to internalize character values from an early age, one of which is through the Islamic storytelling method as explained in the thought of Fāyiz bin 'Abd al-Karīm al-Fāyiz. This research uses a library research approach with primary sources in the form of the book Dawr Mu'allim at-Tarbiyah al-Islāmiyyah fī Tarbiyah a ṭ-Ṭ ullāb by al-Fāyiz, and supported by various relevant scientific journal articles. Data analysis was carried out using the Krippendorff model content analysis technique through the stages of unitization, sampling, coding, data reduction, inference, and drawing conclusions. The results of the study show that the method of al-qiṣaṣ al-hādifah (purposeful Islamic storytelling) is effective in internalizing religious and moral values in early childhood, building empathy and encouraging behavioral transformation through emotional involvement in stories. The success of this method is greatly influenced by the role of the teacher as a mu'addib who is able to bring the narrative to life as well as become a moral example for students.